THE RELATIONSHIP BETWEEN FESTIVAL ATTACHMENT AND ARAB TOURISTS’ REVISIT INTENTION: A CONCEPTUAL MODEL - Mu’ath Hesham Al-Azzam; Ahmad Edwin Mohamed; Lim Khong Chiu (JOURNAL OF TOURISM, HOSPITALITY AND ENVIRONMENT MANAGEMENT (JTHEM), 2024)
While there is a large body of literature on revisit intention to festivals, there is surprisingly little knowledge about it in the context of the Arab world. This research aims to develop a conceptual framework that focuses on the relationship between festival attachment and revisit intentions to festivals. The concept of festival attachment in the current research is borrowed from the concept of place attachment, referring to the same bonds that form between tourists and a tourist place that can also be developed or forged between tourists and a festival. Tourists have an opportunity to develop self-identification with festivals, create affective bonds with them, satisfy and meet their needs through specific facilities or attributes of festivals, and form social bonds with other tourists visiting them, just as they would at a tourist place. All of these aspects together represent what we call attachment to a festival or festival attachment. Based on extensive literature review, the researchers proposed that festival attachment is a multidimensional construct that comprises four dimensions: festival identity, festival affect, festival dependence, and social bonding. The current proposed model will be empirically tested in the context of Jerash Festival of Culture and Arts in Jordan from the perspective of Arab tourists. The findings of this research are expected to broaden the scope of the existing literature on place attachment by introducing important insights from festival settings and its relationship with revisit intention, as well as adding new insights about the Arab tourists’ attachment to cultural festivals and their revisit intentions to these festivals.